Boron nitride nanomaterials with different morphologies: Synthesis, characterization and efficient application in dye adsorption. Issue 9 (November 2015) - Singla, Preeti; Goel, Neetu; kumar, Vinod; Singhal, Sonal
Abstract: Novel boron nitride (BN) nanomaterials with unique and unprecedented properties such as semiconductor with constant band gap, high chemical stability, high thermal conductivity and excellent mechanical properties have been successfully fabricated in the present work in different morphologies as BN nanoparticles and BN nanosheets. Solid state high temperature chemical reactions were adopted for their engineering and various techniques like powder Fourier transform infrared spectroscopy, X-ray diffraction technique and high resolution transmission electron microscopy were employed to examine their morphology and other physicochemical properties. The FT-IR spectra revealed the presence of the B–N bond stretching and bending of B–N–B bond. The hexagonal structure of these BN nanomaterials was divulged from the XRD data, while their different morphology and size were depicted from the high resolution transmission electron microscopy. The nanoparticles are found to be spherical with average diameter of~30 nm and the BN sheet is two dimensional with average thickness of~0.90 nm. The lattice interplaner distance of 3.30 Å determined by high resolution transmission electron microscopy is in good agreement with that of calculated using XRD data. The high surface areas as calculated from the BET analysis are 120.68 m 2  g −1 and 50.02 m 2  g −1 for BN nanoparticles and BN nanosheets respectively. The present work also reports the adsorption behaviour of the synthesized BN nanomaterials towards the adsorption of two different dye molecules, namely, brilliant green and methyl orange. The adsorption conditions have been optimized by varying a number of experimental parameters such as initial dye concentration, adsorbent dosage, pH and time. The interactions of dye molecules with the adsorbate nanomaterials, nature of feasibility of adsorption process have been understood by performing calculations within the formalism of density functional theory at B3LYP/6-31G level of theory.